The Interrelations of ICT and Professional Identity: Studying Group Formations in the Context of Higher Education - Horn, Line Helverskov (Proceedings of the International Conference on Networked Learning, 2016)
The currents of post-modernist thought during the late 20th century spurred an interest in identity as an object of scholarly exploration, as the massive social changes in this period revealed the instable nature of identity. Thus, the study of professional identity has been a recurrent theme in educational science through the last couple of decades, exploring the characteristics and development of professional identity. Simultaneously, the technological development in society has massively affected how we live and our work practices, increasing the intensity of Information and Communication Technology adoption and application of professionals. Educational practices of higher education are equally affected. New educational programmes emerge and course titles, pedagogies, and curricula are adapted to reflect technological changes. Thus, ICT has become a significant aspect of the content and practices of professions and disciplines, and consequently higher education. There is a lack of knowledge with regards to how professional identity are affected by developments and adoption of ICTs in society in general and higher education specifically. The author of this paper suggest Actor-Network Theory as an approach in understanding how Information and Communication Technologies contribute to the characteristics of professional identity in higher education. In the study of how actors are given an identity, the nature of groups is perceived as an on-going process made up of ties. Based on this approach, the study of professional identity must focus on the tracing of associations between heterogeneous actors and their practices. The nature or identity of the group is described through the mapping of spokespersons, anti-groups, boundaries and the inclusion of other professionals such as social scientists and statistics. When studying professional identity in the context of higher education, actors include but is not limited to students, educators, graduates, experienced professionals, but equally tools (including ICTs), curricula, professional legislation and employment statistics. The number or nature of the actors included in the mapping of ties cannot be defined from the outset. The approach will allow the voices of the actors to be heard in characterizing the social context of professional identity, revealing a multitude of perspectives. The author suggests future studies that will engage in higher education practices empirically, developing the theoretical contribution and thus elaborating our understanding of the interrelations of ICT and professional identity as well as serving as a contribution to the body of ANT literature.